Analisis Pengaruh Investment Opportunity Set (Ios), Struktur Modal, dan Size terhadap Kebijakan Dividen pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - B11111037, YENNI RAHMA HARAHAP (Jurnal Manajemen Update, 2015)
Dividend policies are related to issues of profits of the use profits which are the right of shareholders, whether such profits are distributed as dividends or retained be reinvested. This research was conducted to analyze the influence of Investment Opportunity Set (IOS), Capital Structure, and Size on Dividend Policies of the companies listed on Indonesian Stock Exchange during the period of 2010-2013.The sampling technique used was the purposive sampling with the criteria as follows (1) the companies whose shares were actively on Indonesian Stock Exchange; (2) the companies that presented financial statement as of December 2010-2013; and (3) the companies that continously distributed dividends as of December 2010-2013. The data were obtained from the publication of the Indonesia Capital Market Directory (ICMD 2013). A total of 19 out of 137 companies listed on Indonesian Stock Exchange. The analysis technique used was the multiple regression.The result of the research each variable indicated that the Investment Opportunity Set (IOS) and Size had a significant influence with a positive coefficient on the Dividend Policies, while the Capital Structure had no significant influence with a negative coefficient on the Dividend Policies. The result showed that the Investment Opportunity Set (IOS), Capital Structure, and Size simultaneously had a significant influence on the dividend policies. The prediction capability of the three variables on the dividend policies was 32.1% as indicated by the amount of adjusted R-square of 32.1% while the remaining 67.9% was influenced by other factors not covered in the reseach model.Keywords: Investment Opportunity Set, Capital Structure, Size, Dividend Policies.